2019
DOI: 10.1080/24750263.2019.1629030
|View full text |Cite
|
Sign up to set email alerts
|

Make it simple: mating behaviour ofEuphydryas aurinia provincialis(Lepidoptera: Nymphalidae)

Abstract: Courtship in butterflies can vary among species, from simple to elaborate displays, which are thought to promote conspecific mating and drive a female, at first unreceptive, to eventually mate. In this paper, we studied the courtship behaviour of a population of E. aurinia provincialis (Nymphalidae) of the Italian region Latium, finding clear differences in acceptance/refusal of females and in consequent departure/persistence of males. Despite the presence of a period of female unreceptivity after eclosion, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Such a setting allows patrolling males to spot freshly hatched virgin females and at the same time, the unmated females to approach perching males. The latter consideration may deserve further attention, because Pinzari et al (2019) observed that a fraction of females of Euphydryas aurinia provincials (Boisduval, 1828) mate a few days after emergence. The location of perches away from host plants indicates that perching males unlikely harass females seeking for oviposition, a situation described for L. hippothoe by Turlure and Van Dyck (2009), but does not exclude potential harassment of females by patrolling males.…”
Section: Discussionmentioning
confidence: 99%
“…Such a setting allows patrolling males to spot freshly hatched virgin females and at the same time, the unmated females to approach perching males. The latter consideration may deserve further attention, because Pinzari et al (2019) observed that a fraction of females of Euphydryas aurinia provincials (Boisduval, 1828) mate a few days after emergence. The location of perches away from host plants indicates that perching males unlikely harass females seeking for oviposition, a situation described for L. hippothoe by Turlure and Van Dyck (2009), but does not exclude potential harassment of females by patrolling males.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the marsh fritillary butterfly Euphyas aurinia, unreceptive females display a refusal signal with wide wing fluttering and wing fanning, an indication of chemical signaling. Males typically respect this signal; those that persist rarely achieve mating (Pinzari et al, 2019). In the small copper butterfly Lycaeas phlaeas daimio whose females mate only once in their life, unreceptive females display wing closing as a refusal signal.…”
Section: Discussionmentioning
confidence: 99%
“…In this framework, in the context of an ongoing survey of the Lepidoptera fauna in Italy (Pinzari et al, 2010(Pinzari et al, , 2018a(Pinzari et al, , 2018b(Pinzari et al, , 2019aPinzari & Sbordoni, 2013;Pinzari, 2016a;Pinzari & Pinzari, 2019a, 2019b, 2019c, we extensively investigated many aspects of biology of a population of E. aurinia provincialis living in Central Italy: larval host plants preference, predators, adult population dynamics, mating behaviour and parasitoids (Pinzari, 2016b(Pinzari, , 2019Pinzari et al, 2016Pinzari et al, , 2017Pinzari et al, , 2019aPinzari et al, , 2019b.…”
Section: Introductionmentioning
confidence: 99%